UJI TOKSISITAS AKUT EKSTRAK ETANOL KLIKA KAMANDRAH (CROTON TIGLIUM L.) TERHADAP LARVA ARTEMIA SALINA LEACH DENGAN METODE BRINE SHRIMP LETHALITY TEST - Rusman; A. Suparlan Isya Syamsu; Jasmiadi; Sri Wahyuni Gaffar (Journal Prima Health Science, 2020)
Research on the acute toxicity test on an ethanol extract of camandrah clika (Croton tiglium L.) ethanol extract onArtemia salina Leach larvae was conducted. With the Brine Shrimp Lethality Test method. The aim of this researchwas to determine the acute toxicity potential of the camandrah clika ethanol extract that extracted by macerationwith 96% ethanol solvent, then evaporated to produce a thick extract, then it was tested against Artemia salina Leachlarvae at concentrations of 1000 ppm, 100 ppm, ten ppm, one ppm and negative control of seawater. The resultsobtained were based on an analysis of 3,706/mL, classified as highly toxic to the level of Artemia salina Leach.